A novel HIF1AN substrate KANK3 plays a tumor‐suppressive role in hepatocellular carcinoma. (15th November 2017) - Kim, Iljin; Kang, Jengmin; Gee, Heon Yung; Park, Jong‐Wan
Abstract: The KN motif and ankyrin repeat domain‐containing protein (KANK) family is involved in actin cytoskeleton organization and cell motility. Compared with other KANK members, the biological function of KANK3 is not clear. Here, we identified KANK3 as a new substrate for the oxygen sensor hypoxia‐inducible factor 1‐alpha inhibitor (HIF1AN), which hydroxylates HIF‐1/2α and other ankyrin repeat domain‐containing proteins at asparagine residues. An in vitro hydroxylation assay clearly demonstrated asparaginyl hydroxylation of KANK3 by HIF1AN, and mass spectroscopic analysis revealed that KANK3 is hydroxylated at three asparagine residues within the ankyrin repeat domain. Bioinformatics analysis revealed that KANK3 downregulation is correlated with a poor prognosis in several types of cancers, including hepatocellular carcinoma (HCC). In HCC cells, KANK3 knockdown enhanced cell migration and invasion, while its overexpression inhibited these cell behaviors. Interestingly, such effects of KANK3 were not observed under hypoxic conditions, suggesting oxygen‐dependent activity of KANK3. Based on these data, we propose that KANK3 acts as a tumor suppressor to control cancer behavior in an oxygen‐dependent manner.